The three-dimension preclinical models for ferroptosis monitoring - Meng, Yiming; Sun, Jing; Zhang, Guirong; Yu, Tao; Piao, Haozhe (Frontiers in Bioengineering and Biotechnology, 2022)
As a new programmed cell death process, ferroptosis has shown great potential and uniqueness in experimental and treatment-resistant cancer models. Currently, the main tools for drug research targeting ferroptosis are tumor cells cultured in vitro and tumor models established in rodents. In contrast, increasing evidence indicates that reactivity may differ from modifications in mice or humans in the process of drug screening. With the blossoming of 3D culture technology, tumor organoid culture technology has gradually been utilized. Compared with traditional 2D culture and tumor tissue xenotransplantation, tumor organoids have a significantly higher success rate. They can be cultured quickly and at a lower cost, which is convenient for gene modification and large-scale drug screening. Thus, combining 3D cell culture technology, drug monitoring, and ferroptosis analysis is necessary to develop the impact of ferroptosis-related agents in tumor treatment.